MeToo: Disclosure and Response to Sexual Victimization on Twitter - Bogen, Katherine W.; Bleiweiss, Kaitlyn K.; Leach, Nykia R.; Orchowski, Lindsay M. (Journal of interpersonal violence, 2021)
Communication on Twitter surrounding violence against women often occurs through the use of “hashtags” that allow users to engage in shared discourse. The present study examined utilization of the Twitter hashtag #MeToo, which emerged in 2017 as a method for disclosing personal experiences of sexual victimization. Specifically, the present study sought to clarify how Twitter users utilized the #MeToo tag to disclose and respond to sexual violence by conducting a qualitative analysis of a random sample of tweets using #MeToo (N = 1,660). Survivors frequently prioritized the “who,” “what,” “where,” “when,” “why,” and “how” of personal trauma experiences when disclosing using #MeToo. Twitter users also reflected on the prevalence of violence in society, acted as advocates to highlight the problem of violence against women, called attention to the experiences of other survivors of violence, or utilized the forum in a manner that distracted from survivors’ experiences. The present data highlight the utility of Twitter for raising awareness regarding the prevalence of sexual violence, and providing a space where users can share personal trauma, connect to others with similar experiences, and provide support to others.